A Nitrogen-Doped Graphene/Carbon Nanotube Nanocomposite with Synergistically Enhanced Electrochemical Activity - Chen, Ping; Xiao, Tian-Yuan; Qian, Yu-Hong; Li, Shan-Shan; Yu, Shu-Hong (Advanced materials (Weinheim), 2013)
A new kind of nitrogen‐doped graphene/carbon nanotube nanocomposite can be synthesized by a facile hydrothermal process under mild conditions, which exhibits synergistically enhanced electrochemical activity for the oxygen reduction reaction. This research provides a new route to access a metal‐free electrocatalyst with high activity under mild conditions.